The Legalisation of Child Pornography in Sweden and What Followed (1969-1999) - Svanberg, Mikael (Bergen Journal of Criminal Law & Criminal Justice, 2023)
After some years of debate among intellectuals about the freedom of individuals in relation to the state, sexual intercourse in public was legalised in Sweden in 1971 with an age limit of 15 for participants, and all kinds of printed pornography were legalised without an age limit for those involved. (The representation and private adult consumption of pornography in moving images remained legally unregulated like before.) The reform was similar to a reform that had entered into force in Denmark in 1969. A re-regulation of pornography was carried out during the period 1973-1999. The result of this study shows that although child pornography in print and sexual intercourse in public were criminalised during the rule of conservative Governments (1976-1982), it was not until 1990 that all political parties took a firm stand against child pornography in moving images. The results have been interpreted in the light of the Scandinavian legal realism that characterised Swedish legislation until the 1990s.